The longitudinal association of venue stability with consistent condom use among female sex workers in two Mexico–USA border cities. (July 2013) - Gaines, T L; Rudolph, A E; Brouwer, K C; Strathdee, S A; Lozada, R; Martinez, G; Goldenberg, S M; Rusch, M L A
Summary: We examined the relationship between venue stability and consistent condom use (CCU) among female sex workers who inject drugs (FSW-IDUs; n = 584) and were enrolled in a behavioural intervention in two Mexico–USA border cities. Using a generalized estimating equation approach stratified by client type and city, we found venue stability affected CCU. In Tijuana, operating primarily indoors was significantly associated with a four-fold increase in the odds of CCU among regular clients (odds ratio [OR]: 3.77, 95% confidence interval [CI]: 1.44, 9.89), and a seven-fold increase among casual clients (OR: 7.18, 95% CI: 2.32, 22.21), relative to FSW-IDUs spending equal time between indoor and outdoor sex work venues. In Ciudad Juarez, the trajectory of CCU increased over time and was highest among those operating primarily indoors. Results from this analysis highlight the importance of considering local mobility, including venue type and venue stability, as these characteristics jointly influence HIV risk behaviours.